Antimicrobial activity of Hibiscus and Murraya leaf extracts against a variety of multidrug-resistant samples - Pal Neha (Journal of BioScience and Biotechnology, 2024)
This research examined the antimicrobial properties of leaf extracts from Hibiscus rosa sinensis and Murraya koenigii against a range of human pathogenic bacteria, including E. coli, K. pneumoniae, P. aeruginosa, and S. aureus. The study utilized the disc diffusion method to assess the antimicrobial effects of benzene, acetone, and methanol extracts. Results showed that the extracts displayed broad-spectrum antibacterial activity against all of the tested pathogens. The most significant zone of inhibition was observed for P. aeruginosa, E. coli, and S. aureus in the benzene, acetone, and methanol extracts, respectively. Phytochemical screening identified several compounds, including terpenoids, tannins, alkaloids, and flavonoids, which may contribute to the antimicrobial activity of the plants. In conclusion, Hibiscus rosa sinensis and Murraya koenigii could be valuable sources of antibacterial agents against K. pneumoniae, E. coli, P. aeruginosa, and S. aureus.